Utilization of Ketapang Leaf Extract (Terminalia catappa) on Water Physics Parameters and Seed Growth of Jelawat (Leptobarbus hoeveni) - Sari, Alfiah; Pamukas, Niken Ayu; Firmansyah, Rodhi (Jurnal Akuakultur SEBATIN, 2026)
Ketapang (Terminalia catappa) leaf solution plays an important role in water quality and the growth of catfish. This research was conducted in May 2023 at the Environmental Quality Laboratory of Aquaculture, Faculty of Fisheries and Marine Sciences, Universitas Riau. This study aims to determine the effect and get the best dose of ketapang leaf solution on the physics parameters of water growth media for catfish. This study used a completely randomized design (CRD) method with four treatments and three replicates, the size of the fish used in this study was 4-6 cm. The results of the research that has been done are the provision of ketapang leaf solution gives an influence on the concentration of pH, growth, and survival rate. The best treatments was obtained in P2 (4 g/L) with pH value (7.19±0.04), absolute length (0.93 cm), absolute weight (1.47 g), and survival rate (96.67%).